Answer:
-2 × (7x + 1) -5 × (3x² + 3x + 2) is equivalent to -15x² - 29x - 12 .
(-7x² -21x + 13) - (8x² + 8x + 25) is equivalent to -15x² - 29x - 12 .
Explanation:
As given the expression in the question be as follow .
= -15x² - 29x - 12
First part
= (-19x² -4x -7) + (4x² + 25x - 5)
First open the bracket
= -19x² -4x -7+ 4x² + 25x - 5
= -19x² + 4x² -4x + 25x -7 - 5
= -15x² +21x - 12
Thus (-19x² -4x -7) + (4x² + 25x - 5) is not equivalent to -15x² - 29x - 12 .
Second part
= (-17x² + 2x -3) + (2x² - 31x - 9)
First open the bracket
= -17x² + 2x² + 2x -31x -3 -9
= -15x² - 29x - 12
Thus (-17x² + 2x -3) + (2x² - 3x - 9) is not equivalent to -15x² - 29x - 12 .
Third part
= -2 × (4x - 15) -3 × (5x² + 7x + 6)
First open the bracket and simplify the above terms
= -8x + 30 -15x² -21x -18
= -15x² -29x + 12
Thus -2 × (4x - 15) -3 × (5x² + 7x + 6) is not equivalent to -15x² - 29x - 12 .
Forth Part
= (5x² - 10x + 8) - (10x² + 19x + 20)
First open the bracket
= 5x² - 10x² - 10x - 19x + 8 - 20
= -5x² - 29x -12
Thus (5x² - 10x + 8) - (10x² + 19x + 20) is not equivalent to -15x² - 29x - 12 .
Fifth part
= -2 × (7x + 1) -5 × (3x² + 3x + 2)
First open the bracket
= -14x -2 -15x² -15x -10
= -15x² -29x -12
Thus -2 × (7x + 1) -5 × (3x² + 3x + 2) is equivalent to -15x² - 29x - 12 .
Sixth part
= (-7x² -21x + 13) - (8x² + 8x + 25)
Firsr open the bracket
= -7x² -21x + 13 - 8x² - 8x - 25
= -15x² -29x - 12
Thus (-7x² -21x + 13) - (8x² + 8x + 25) is equivalent to -15x² - 29x - 12 .